2017
DOI: 10.1051/0004-6361/201730728
|View full text |Cite
|
Sign up to set email alerts
|

The habitability of a stagnant-lid Earth

Abstract: Context. Plate tectonics is considered a fundamental component for the habitability of the Earth. Yet whether it is a recurrent feature of terrestrial bodies orbiting other stars or unique to the Earth is unknown. The stagnant lid may rather be the most common tectonic expression on such bodies. Aims. To understand whether a stagnant-lid planet can be habitable, i.e. host liquid water at its surface, we model the thermal evolution of the mantle, volcanic outgassing of H 2 O and CO 2 , and resulting climate of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
129
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(132 citation statements)
references
References 155 publications
(249 reference statements)
3
129
0
Order By: Relevance
“…This scenario fits in very nicely with the recent work of (Weller & Kiefer, 2019) who give a timescale of order 1Gyr for the transition from a mobile to a stagnant lid mode on Venus in their simplified model. Without a mechanism to efficiently cycle volatiles in a stagnant lid mode (e.g., Tosi et al, 2017;Höning et al, 2019), outgassing would have continued without the major weathering and subduction surface sinks that operate on Earth, hence CO 2 and N 2 would build up over time to reach the levels we see on Venus today. Some studies have also shown that even in a stagnant lid mode it is possible to cycle volatiles, possibly up to gigayears in time (e.g., Foley & Smye, 2018;Godolt et al, 2019), but these mechanisms depend on the initial CO 2 budget and the retention of at least some water after cooldown.…”
Section: )mentioning
confidence: 99%
“…This scenario fits in very nicely with the recent work of (Weller & Kiefer, 2019) who give a timescale of order 1Gyr for the transition from a mobile to a stagnant lid mode on Venus in their simplified model. Without a mechanism to efficiently cycle volatiles in a stagnant lid mode (e.g., Tosi et al, 2017;Höning et al, 2019), outgassing would have continued without the major weathering and subduction surface sinks that operate on Earth, hence CO 2 and N 2 would build up over time to reach the levels we see on Venus today. Some studies have also shown that even in a stagnant lid mode it is possible to cycle volatiles, possibly up to gigayears in time (e.g., Foley & Smye, 2018;Godolt et al, 2019), but these mechanisms depend on the initial CO 2 budget and the retention of at least some water after cooldown.…”
Section: )mentioning
confidence: 99%
“…The question above relates to the extension of thermal history studies from Earth to planetary application, habitability in particular [Kite et al, 2009, Schaefer and Sasselov, 2015, Komacek and Abbot, 2016, Foley, 2015, Foley and Driscoll, 2016, Tosi et al, 2017, Foley and Smye, 2018, Barnes et al, 2019. Thermal history models applied to the Earth are postdictive: they set out to match historical data.…”
Section: Discussionmentioning
confidence: 99%
“…The contrasting mantle fO2 conditions between both planetary bodies is certainly linked to planetary size (Wade and Wood, 2005). Nevertheless, the H2O/CO2 ratio of volcanic gases during that era was controlled by the atmospheric pressure, with dense atmospheres favoring dry volcanic emissions while tenuous atmospheres favored H2O-rich volcanic gases (Gaillard and Scaillet, 2014;Tosi et al, 2017). This is linked to the fact that H2O is orders of magnitude more soluble than CO2 in basalts and that solubility laws imply that, with decreasing pressure, the faction of water partitioning into the fluid must increase (see Iacono-Marziano et al, 2012).…”
Section: Degassing Volatile Cycles and Continental Cyclingmentioning
confidence: 99%
“…Noteworthy, though this has never been specifically reviewed in the literature, this filtering process by volcanic degassing also applies to sulfur degassing (sulfur-rich magma may not degas sulfurrich gas). All this complicates the planetary degassing picture and introduces feedbacks that seem promising to address and to relate to the concept of formation of the oceans, climate and habitability (Gaillard and Scaillet, 2014;Tosi et al, 2017).…”
Section: Degassing Volatile Cycles and Continental Cyclingmentioning
confidence: 99%
See 1 more Smart Citation